Acts of Complaining as Realized by COVID-19 Survivors in Indonesia: A Gender Perspective - Nur, Nur Lailiyah; Djatmika, Djatmika; Santosa, Riyadi; Sumarlam, Sumarlam (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
Background: The increase in Covid-19 patients in Kediri City has had a significant influence on a variety of areas, including health services in the hospitals. This paper explicates an overview of how Covid-19 patients complain about health services in hospitals. Methodology: The present study employed qualitative design using sociopragmatics approach. Data was collected from 31 informants of different genders. The data analysis used Trosborg’s theory. Findings: The results show that in Situation 1 (Medical Ward), both female and male patients have similarities in the use of speech act of complaining using annoyance by 37% of female and 36% of male patients, while in Situation 2 (Healthcare Services), there are differences in the use of the complaining strategy across gender. Women tend to use the ill consequences strategy (29%), while men used the annoyance strategy (34%). While the pattern of similarity in the speech act of complaining used across genders shows that the hint strategy (1%) was used by both genders as seen in Situation 2. Conclusion: To sum up, the difference in gender is not always a determining factor or benchmark in determining something including language use, it all depends on the individual's character in responding to something. Women can no longer be considered